Correlation between Clinical and Endoscopic Findings in Patients with Dyspepsia at a Tertiary-Care Hospital of Bangladesh - Muslehuddin Shahed, Mohammad; Anwarul Azim, Md; Mohajan, Monisha; Shankar Roy Biswas, Rajat; Yusuf, Muhammad (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Dyspepsia is a prevalent symptom worldwide, affecting 7%-34.2% of populations, and has a significant impact on patients and healthcare systems. The study aimed to investigate the relationship between clinical and endoscopic findings to improve cost-effectiveness in endoscopy. Materials and methods: This observational study was conducted at the Department of Gastroenterology, Chattagram Maa-O-Shishu Hospital Medical College (CMOSHMC) over a period of 34 months from January 2020 to October 2022. Study population was patients aged 18 years and above with dyspepsia symptoms referred from various departments of this hospital for upper gastrointestinal tract endoscopy. Results: The study involved 705 patients, with the largest age group experiencing dyspepsia symptoms being 28-37 years old (25.5%). Dyspepsia was more prevalent in patients below 57 years old (83.1%) compared to those above 57 years old (16.8%). Females had a higher incidence of dyspepsia than males, with a ratio of 1.9:1. Abdominal pain was the most common symptom (43.96%). Endoscopic findings included peptic ulcers (14.6%), gastric ulcer (8.36%), duodenal ulcer (6.24%), gastritis (32.48%), oesophagitis (13.33%), gastric carcinoma (1.84%), and normal results (34.60%). Female gender was associated with normal endoscopic findings (p<0.05). Conclusion: The study concludes that both uninvestigated and functional dyspepsia was more prevalent in females. Abdominal pain was the most common complaint followed by abdominal burning. The study also revealed that prevalence of functional dyspepsia decreases with age, giving way to organic lesions. Gastritis was a frequent endoscopic finding; however, its clinical relevance is uncertain><0.05). Conclusion: The study concludes that both uninvestigated and functional dyspepsia was more prevalent in females. Abdominal pain was the most common complaint followed by abdominal burning. The study also revealed that prevalence of functional dyspepsia decreases with age, giving way to organic lesions. Gastritis was a frequent endoscopic finding; however, its clinical relevance is uncertain. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 31-35